Evaluation of 5 Years Profile of an Infant Cleft Lip and Palate Clinic - Arzu Arı-Demirkaya; Toros Alcan (Galenos Yayinevi, 2007)
The aim of this report was to present the distribution of patients and treatment modalities of all cleft lip and palate (CLP) patients accepted for treatment in the newborn cleft clinic at the Marmara University, Faculty of Dentistry, Department of Orthodontics, during the 5 years from October 2001 to October 2006, and to summarize the structure and organization of the clinic. The goal was to initiate a nationwide exchange of opinions among orthodontic clinics that deal with the treatment of newborn CLP patients, to communicate clinical experience and information, and to make a step forward in standardizing records as a basis for future multicentered research. Even though preoperative orthopedics for newborn cleft lip and palate patients is still a matter of controversy, it has been adopted in our clinic, and the use of feeding plates and nasoalveolar molding is chosen according to the cleft type. Along with the medical history, digital pictures, maxillary and nasal impressions, and written treatment documentation are the basic records. Of the 263 newborn patients who have been accepted for treatment within the last 5 years, only one had a median cleft, 23.2 % were bilateral, 41.8 % were unilateral, 34.6 % were isolated cleft palate patients; while 95 % of the unilateral cases and 85 % of the bilateral cases have been treated via nasoalveolar molding. Patients are being followed up in 6 month intervals after the primary repair, with consultation of a pediatric dentist, a speech therapist, and the surgeon, where necessary. It is obvious that comprehensive cleft care can only be provided by specialists, who dedicate the majority of their time to cleft care in a common separate location and in an interdisciplinary fashion. In order to establish a national health policy that provides optimum conditions and sufficient financial contribution, it is necessary to join specialists all over Turkey in a cleft network and to establish a national data pool as soon as possible.